War by Other Means? Incentives for Power Seekers in Thomas Hobbes's Political Philosophy - Odzuck, Eva (Review of Politics, 2018)
The problem of the power seeker is of crucial importance for Hobbes's political philosophy. While education might aid in changing the behavior of some people, Hobbes is clear that there are limits to the effectiveness of education and that incurable, unsocial power seekers will persist. In my analysis, I ask whether and, if so, how Hobbes can also get these incurable power seekers on board. The result of my findings that Hobbes provides a huge variety of treatments for power seekers, including incentives to betray and exploit their fellow citizens by employing a public gesture of civility, has implications for Hobbes research: it shows the complexity and costs of Hobbes's “solution” to the problem of war and corrects a widespread developmental hypothesis about the concept of honor in Hobbes's works. Thereby, it can also enrich a recent diagnosis about the decline of honor in modern societies.
Keywords: Thomas Hobbes; Political Theory; Power; Education; Rhetoric; Passions; Honor